Liquid crystalline block copolymers by sequential cationic or promoted cationic and free‐radical polymerizations - Galli, Giancarlo; Chiellini, Emo; Yagci, Y.; Serhatli, E. I.; Laus, M.; Angeloni, A. S. (Wiley, 1996)
AbstractThe scope for the study of the synthesis and properties of liquid crystalline (LC) block copolymers is briefly outlined. While there are many approaches to the synthesis of LC block copolymers, the use of azo macroinitiators is very versatile and allows one to produce diverse block copolymer architectures. Azo macroinitiators are prepared by cationic or promoted cationic polymerization of tetrahydrofuran (1) or cyclohexene oxide (2), and are then used to initiate the free‐radical polymerization of various methacrylates 3,4 or acrylates 5–9 containing mesogenic azobenzene or biphenyl units thereby yielding block copolymers. The AB or ABA block copolymers are microphase‐separated and form smectic and/or nematic mesophases similar to the respective LC homopolymers.